KAJIAN BENTUK GUNUNGAN WAYANG SEBAGAI REPRESENTASI BUDAYA INDONESIA PADA VISUAL LOGO HALAL INDONESIA - Dewi Pugersari; Wahyu Arnisa (Kartala Virtual Studies, 2024)
The authority for halal certification in Indonesia was transferred and followed by a change in the national halal logo. The new halal logo raises pros and cons; one of the reasons is the shape of the logo design, which is considered not to represent the culture of Indonesia but only Javanese culture. This research was conducted to examine the existence and shape of gunungan wayang in various regional cultures in Indonesia. Study of the shape of gunungan wayang as a representation of Indonesian culture on the visual on the Indonesian halal logo. The purpose of this study is to examine the visual suitability of gunungan wayang shape on the Indonesian halal logo as a representation of Indonesian culture. Qualitative research using descriptive methods based on Erwin Panofsky’s iconography theory was carried out by researchers supported by literature review and observations. Based on research, it is known that gunungan wayang in various regions of Indonesia originates from Javanese culture and it can be found on 4 of the 6 big islands in Indonesia; Java Island, Bali Nusa Island, Sumatera Island, and Kalimantan Island. There it can be concluded the visual shape of gunungan wayang in the Indonesian halal logo can represent Indonesian culture. In particular, it has a strong influence on Javanese culture, especially the visual shape of gunungan wayang used in the Indonesian halal logo the Javanese gunungan wayang.